(untitled) (Bangladesh Journal of Botany, 2022)
The root distribution pattern, growth and yield of guava were studied on the trees planted at 3 m × 3 m spacing on raised bed whose basin area was covered with black polythene mulch (RBM), raised bed without mulch (RBUM) and flat bed (FB). Findings showed that the root density varied in horizontal and vertical position. Maximum feeding roots (< 2mm thickness) were recorded up to 20 cm radial distance from tree trunk at 0-15 cm depth under raised bed with mulch (RBM) and without mulch (RBUM) conditions. However, at 16-30 cm depth, fibrous roots (< 2mm thickness) were found uniform in all the growing conditions of the tree. Root mass of 2-5 mm thick were found significantly higher (1.84 g) in 0-15 cm depth at 20 cm radial distance from trunk. Maximum (1.62g) root mass (2-5 mm thick roots) was noted in 16-30 cm depth at 40 cm radial distance from trunk in RBM, while the lowest in flat bed. Root mass of 2-5 mm thick roots were found similar in 0-15 and 16-30 cm depth at 60 and 80 cm radial distance. Canopy spread, collar diameter and yield per tree were recorded maximum in the tree grown at RBM condition. Bangladesh J. Bot. 51(1): 131-138, 2022 (March)